Nonlinear System Identification of Laboratory Heat Exchanger Using Artificial Neural Network Model - Nader Jamali Soufi Amlashi; Amin Shahsavari; Alireza Vahidifar; Mehrzad Nasirian (Institute of Advanced Engineering and Science, 2013)
This paper addresses the nonlinear identification of liquid saturated steam heat exchanger (LSSHE) using artificial neural network model. Heat exchanger is a highly nonlinear and non-minimum phase process and often its working conditions are variable. Experimental data obtained from fluid outlet temperature measurement in laboratory environment is used as the output variable and the rate of change of fluid flow into the system as input too. The results of identification using neural network and conventional nonlinear models are compared together. The simulation results show that neural network model is more accurate and faster in comparison with conventional nonlinear models for a time series data because of the independence of the model assignment.DOI:http://dx.doi.org/10.11591/ijece.v3i1.1954